History Walks in New Jersey - Rosenfeld, Lucy D. (JSTOR EBA., 2006)
New Jersey has a varied and fascinating history-from its earliest Native American settlements, through its central role in the Revolutionary War, to its strategic position in the major events of our country's past. In History Walks in New Jersey, Lucy D. Rosenfeld and Marina Harrison treat readers to a comprehensive statewide guidebook that includes detailed information on forty-eight of the best sites for historical walks. These outings take the history enthusiast through beautiful green landscapes, natural preserves, and picturesque settlements. Whether you are an amateur historian, a weekend walker, or a teacher planning a class trip, this book will be an essential resource for ideas and information. Walks include the Kingston Loop, a long canal where George Washington, pen in hand, composed his post-Revolutionary War speech, "Farewell Orders to the Armies of the United States." Also included is a mountain walk that traces Native American Leni-Lenape history and one that wends its way into an old Moravian village in the town of Hope. A pirate cove, stops on the Underground Railroad, a Civil War cemetery, and the sites of duels, mines, canals, architectural innovations, estates and resorts, centuries-old agricultural and fishing settlements, and the Hindenburg crash are all here. Each walk includes directions, information on tours, a brief history, and suggestions for additional places to visit in the area. Whether a New Jersey native or a visitor to the Garden State, readers will enjoy going beyond the highways and suburban towns to learn about history while discovering the state's natural beauty.